Komunikasi Dalam Kepemimpinan Organisasi - Mu’alimin Mu’alimin; Larasati Afina Salsabilla; Sahawtul Jannah; Mohammad Zen Amrullah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Effective communication has a very important role in the success and performance of leaders in an organization. Focus on the strategies used to improve communication. Communication in an organization covers various aspects, including internal communication between leaders, team members, and departments. Thus, a deep understanding of the role of communication in organizational leadership becomes a real effort to improve communication and make a significant contribution to achieving organizational goals and improving overall performance. This research aims to explain communication in organizational leadership. This literature review was obtained from scientific research articles from 2018-2023 using Google Scholar in Publish or Perish (PoP) with the keywords